Effects of Videomodeling and Written Instructions on the Caregiving Behaviors of Elderly Individuals - Lima, Letícia Maria Leão; Gonçalves, Aparecida Tereza de Anchieta Ferreira; Silva, Álvaro Júnior Melo e; Lima, Jeisiane dos Santos (Perspectivas em Análise do Comportamento, 2024)
Current demographic indices point to a global trend of aging populations. In this sense, the demand for professions linked to the care of elderly individuals is growing and educational interventions structured from Psychology and Applied Behavior Analysis can enable research aimed at disseminating practical knowledge in the provision of care. In the present study, the objective was to verify the effectiveness of two forms of intervention, for caregivers of elderly people, which are: video modeling and written instructions on the percentage of emission of appropriate care behaviors in feeding and transfer situations. This is an experimental study conducted in a Long-Term Institution for the Elderly through an educational intervention applied to caregivers who work at the institution. Three formal caregivers participated in the study and the procedure was carried out in four stages: probe, baseline, intervention and post-test. In the intervention, material with written instructions or video modeling was presented, randomly among the participants, that is, each participant was presented with only one instructional material. As a result, there was an increase in the emission of care behaviors considered appropriate, regardless of the intervention strategy used. The effectiveness of the teaching strategies used to modify the pattern of care behaviors of the study participants is discussed.